Pengaruh Solvabilitas dan Kebijakan Dividen Terhadap Harga Saham Perusahaan LQ45 - Dwi Ratna Anjani; Sutanti Sutanti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The purpose of this study is to analyze "The Effect of Solvency and Dividend Policy on Stock Prices of Companies Listed in the LQ45 Index. This study uses a quantitative approach and is associative. The population of this study consists of the 45 largest companies in Indonesia that have good financial reports. Sampling can be done using the Purposive Sampling technique, so that 12 companies can be obtained as samples. The data analysis technique used is multiple linear regression. The results of the study show that Solvency has a negative and insignificant effect on Stock Prices, while Dividend Policy has a positive and significant effect on Stock Prices.